2022
DOI: 10.3390/ijms232415921
|View full text |Cite
|
Sign up to set email alerts
|

Anp32a Promotes Neuronal Regeneration after Spinal Cord Injury of Zebrafish Embryos

Abstract: After spinal cord injury (SCI) in mammals, neuronal regeneration is limited; in contrast, such regeneration occurs quickly in zebrafish. Member A of the acidic nuclear phosphoprotein 32 (Anp32a) family is involved in neuronal development, but its function is controversial, and its involvement in zebrafish SCI remains unknown. To determine the role of zebrafish Anp32a in the neuronal regeneration of SCI embryos, we microinjected Anp32a mRNA into embryos from zebrafish transgenic line Tg(mnx1:GFP) prior to SCI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…A previous study reported that radial glial cells (RGs) can promote neuronal regeneration in the CNS of zebrafish [ 67 , 68 , 69 ]. RGs in zebrafish efficiently repair lesions after injury to the telencephalon through the induction of serval processes.…”
Section: Macrophage Tnf-α Signaling May Regulate Radial Glial Cell-me...mentioning
confidence: 99%
“…A previous study reported that radial glial cells (RGs) can promote neuronal regeneration in the CNS of zebrafish [ 67 , 68 , 69 ]. RGs in zebrafish efficiently repair lesions after injury to the telencephalon through the induction of serval processes.…”
Section: Macrophage Tnf-α Signaling May Regulate Radial Glial Cell-me...mentioning
confidence: 99%
“…However, even with axonal regeneration, functional recovery remains limited due to the challenges in integrating regenerative axons into existing neural circuits and reestablishing functional synaptic connections ( Figure 1 ). Zebrafish studies have already yielded valuable information on potential candidate proteins involved in neuroregeneration following SCIs, such as CTGFa [ 132 ], Cav1 [ 51 ], ANP32a [ 133 ], matrix metalloproteinase-9 [ 158 ], and sonic hedgehog [ 159 , 160 ]. Furthermore, in the current zebrafish study, differentially expressed genes were sorted and analyzed in-depth using bioinformatics methods, such as the Notch signaling pathway [ 161 , 162 ], Wnt signaling pathway [ 163 ], and Hippo-Yap/Taz signaling pathway [ 164 ].…”
Section: Future Directions: Zebrafish Neuron Regeneration Research In...mentioning
confidence: 99%
“…Zeng et al (2021) found that Caveolin 1 (Cav1), a membrane protein, was significantly upregulated in the rostral side of glial cells at the injury region and was responsible for axonal regrowth [51]. Lee et al (2022) discovered that acidic nuclear phosphoprotein 32 family member A (ANP32a) played a positive role in the regeneration of zebrafish embryos with SCIs [133].…”
Section: Zebrafish Present An Opportunity To Study Neural Regeneratio...mentioning
confidence: 99%